Brittle rupture of an aged HPDE geomembrane at local gravel indentations under simulated field conditions. Issue 1 (1st February 2014) - Abdelaal, F.B.; Brachman, R.W.I.; Rowe, R.K.
Abstract : ABSTRACT: The susceptibility of a 1.5 mm thick high-density polyethylene geomembrane to brittle rupture from long-term stress cracking in a simulated municipal solid waste landfill liner is examined. The geomembrane was pre-aged in a leachate at 85°C to lower the notched constant tensile load stress crack resistance of the geomembrane to about 75 h. The aged geomembrane was then used as part of a composite liner system in geosynthetic liner longevity simulators (GLLSs) with a geosynthetic clay liner and sand foundation layer below the geomembrane and a 560 g/m 2 geotextile protection layer and 50 mm drainage gravel above the geomembrane. The GLLSs allow the simulation of field conditions including elevated temperatures, overburden pressure, leachate circulation, and composite liner exposure conditions. The geomembrane experienced brittle rupture on the side slopes of the local gravel indentations for temperatures between 55 and 85°C. The higher the liner temperature, the shorter the time to rupture and the higher the tensile strain at rupture. Arrhenius modelling of the test data gave an activation energy of E a = 112 kJ/mol.